Long-Term Consumption of Cuban Policosanol Lowers Central and Brachial Blood Pressure and Improves Lipid Profile With Enhancement of Lipoprotein Properties in Healthy Korean Participants - Kim, Suk-Jeong; Yadav, Dhananjay; Park, Hye-Jeong; Kim, Jae-Ryong; Cho, Kyung-Hyun (Frontiers in Physiology, 2018)
Metabolic syndrome is closely associated with higher risk of hypertension, cardiovascular disease, diabetes and stroke. The aim of the present study was to investigate the long-term effects of policosanol supplementation on blood pressure (BP) and the lipid profile in healthy Korean participants with pre-hypertension (systolic 120-139 mmHg, diastolic 85-89 mmHg). This randomized, double-blinded, and placebo-controlled trial included 84 healthy participants who were randomly assigned to three groups receiving 10 mg of policosanol, 20 mg of policosanol, or placebo for 24 weeks. The BP, lipid profile, and anthropometric factors were measured pre- and post-intervention and then compared. Based on an average of three measurements of brachial BP, the policosanol 20 mg group showed the most significant reduction in average systolic BP (SBP) from 140±12 mmHg at week 0 to 126±13 mmHg at week 24 (p<0.0001). The policosanol 20 mg group also showed significant reductions in aortic SBP and DBP up to 9% (p=0.00057) and 8% (p=0.004), respectively compared with week 0. Additionally, blood renin and aldosterone levels were significantly reduced in the policosanol 20 mg group up to 63% (p<0.01) and 42% (p<0.05), respectively, at week 24. For the blood lipid profile, the policosanol 10 mg and 20 mg groups showed significant reductions in total cholesterol (TC) of around 8% (p=0.029) and 13% (p=0.0004), respectively, at week 24 compared with week 0. Serum HDL-C level significantly increased up to 16% and 12% in the policosanol 10 mg (p=0.002) and 20 mg (p=0.035) group, respectively. The study results suggest that long-term policosanol consumption simultaneously reduces peripheral BP as well as aortic BP accompanied by elevation of HDL-C and % HDL-C in TC in a dose-dependent manner.